1998
DOI: 10.1177/03635465980260030301
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Load Eccentric Calf Muscle Training For the Treatment of Chronic Achilles Tendinosis

Abstract: We prospectively studied the effect of heavy-load eccentric calf muscle training in 15 recreational athletes (12 men and 3 women; mean age, 44.3 7.0 years) who had the diagnosis of chronic Achilles tendinosis (degenerative changes) with a long duration of symptoms despite conventional nonsurgical treatment. Calf muscle strength and the amount of pain during activity (recorded on a visual analog scale) were measured before onset of training and after 12 weeks of eccentric training. At week 0, all patients had A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
863
6
44

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,035 publications
(928 citation statements)
references
References 19 publications
15
863
6
44
Order By: Relevance
“…Exercise is important in both prevention and treatment of tendinopathy. Eccentric exercise therapy has been reported to have some effect in prospective, randomized trials in athletic patients; 54,55 however, a review of 20 published trials found that there was little evidence of a positive effect on clinical outcomes, such as reduction of pain, return to function and patient satisfaction. 56 Shock-wave therapy, which is thought to function on the tenocytes to stimulate repair, might be effective in a carefully selected group of patients, 57 although other studies have reported no significant effect.…”
Section: New Treatments For Tendinopathy and Future Research Directionsmentioning
confidence: 99%
“…Exercise is important in both prevention and treatment of tendinopathy. Eccentric exercise therapy has been reported to have some effect in prospective, randomized trials in athletic patients; 54,55 however, a review of 20 published trials found that there was little evidence of a positive effect on clinical outcomes, such as reduction of pain, return to function and patient satisfaction. 56 Shock-wave therapy, which is thought to function on the tenocytes to stimulate repair, might be effective in a carefully selected group of patients, 57 although other studies have reported no significant effect.…”
Section: New Treatments For Tendinopathy and Future Research Directionsmentioning
confidence: 99%
“…One study reports that 89% of the runners with Achilles tendinopathy were men (Kvist, 1991). In a review of several treatment studies, the percentage of men was between 45-86%, with the lower percentages seen in the more recent studies (Nelen et al, 1989, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Alfredson and Öhberg, 2005d.…”
Section: In a Populationmentioning
confidence: 99%
“…Studies of the effect of strengthening exercise on tendon are almost non-existent, apart from a study by Simonsen and coworkers (1995), who found no effect from strength training on tendon in rats. Strength training has, however, been shown to have positive effect on injuries to the Achilles tendon (Niesen-Vertommen et al, 1992, Alfredson et al, 1998b, Mafi et al, 2001, Silbernagel et al, 2001, Alfredson et al, 2001a, Roos et al, 2004. Endurance type exercise might, however, not have the same effect as strengthening exercise on tendon.…”
Section: Effect Of Exercise On Tendonsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Eccentric exercise is benefi cial in evoking gains in muscle power and muscle spring stiffness, 21,22 increasing stiffness in the tendon, preventing injury to the muscletendon unit and the tendon itself, 21 and reducing pain associated with tendon disorders. 21,23,24 The advantages of eccentric exercise compared to concentric exercise are reduction of metabolic costs and O 2 consumption, 3,25 production of much greater force (i.e., two-to threefold) than that of concentric exercise, 26 and a better remodeling response. Ischemia and local hypoxia are thought to be major stimuli for VEGF-induced angiogenesis.…”
mentioning
confidence: 99%